Identyfikacja ryzyka projektu logistycznego - Marek, Robert (Risk Identification in Logistic Projects, 2008)
The logistic companies, in the presence of changing environment and growing competition, shall continuously improve the way of managing with a special regard to risk identification. These kinds of decisions ought to be treated as key because they settle a question about the development of logistic companies. Therefore the risk's identification shall be conducted with the best practice in a company which undertakes new capital intensive logistic projects. As a result in the paper is taken up the discussion on risk identification connected with the logistic project.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 107-116